2008
DOI: 10.1007/s11655-008-0194-1
|View full text |Cite
|
Sign up to set email alerts
|

Menopause in German and Chinese women—An analysis of symptoms, TCM-diagnosis and hormone status

Abstract: German and Chinese menopausal women do not show different prevalence but have different patterns of menopausal symptoms. Furthermore, from a TCM point of view, German women suffer more from Shen-yang deficiency whereas Chinese women suffer more from Shen-yin deficiency syndrome. These results are supported by significantly lower levels of testosterone in German women compared to Chinese women, which, in TCM, is a characteristic of yang deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Most of the people recruited in our study were between 20 and 55 years old, change of Yang-qi during this age group may follow a bell-shaped pattern, thus Yang-Deficient Consitution was proved to have no linear correlation with age in this study. Whether the correlation between Yang-Deficient Consitution and gender was due to sex hormonal level needs further elucidation [27, 28]. Malnutrition is also a factor to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the people recruited in our study were between 20 and 55 years old, change of Yang-qi during this age group may follow a bell-shaped pattern, thus Yang-Deficient Consitution was proved to have no linear correlation with age in this study. Whether the correlation between Yang-Deficient Consitution and gender was due to sex hormonal level needs further elucidation [27, 28]. Malnutrition is also a factor to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the studies identify women who chose TCM to treat menopausal symptoms as commonly experiencing vasomotor symptoms (hot fl ushes and night sweats) 32,33,39,40,42,43,49,52 , and emotional changes (depression, anxiety and irritability) 32,33,40,43,52 . These two sets of symptoms are thus regarded as the most relevant complaints, followed by dryness of mouth/eyes 32,33,39,43 , sleeplessness 32,33,40,43 , and headache 32,33,38,40 .…”
Section: Patient/user-focused Data: Motivation For and Perception Of mentioning
confidence: 99%
“…These two sets of symptoms are thus regarded as the most relevant complaints, followed by dryness of mouth/eyes 32,33,39,43 , sleeplessness 32,33,40,43 , and headache 32,33,38,40 . TCM was regarded as a ' supplementary method ' for some Chinese Singaporean menopausal women when managing abnormal menstrual bleeding 52 .…”
Section: Patient/user-focused Data: Motivation For and Perception Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet recently researchers outside China have demonstrated that the TCM syndromes can be observed in patients who are not of Chinese origin. For instance, evidence was observed in the distribution of similar TCM syndromes in Australian and Chinese women with primary dysmenorrhoea ; the Shen deficiency syndrome could be diagnosed in both German and Chinese menopausal women under the same diagnostic criteria (Rampp et al, 2008). TCM syndrome differentiation, if adopted as the diagnostic method for the substantial part in modern TCM research, would lead to new scientific findings for medical sciences.…”
Section: Introductionmentioning
confidence: 99%